Using Environmentally-Themed Videos to Help Extension Promote Good Landscape Management Behaviors: AEC639/WC302, 5/2018 - Warner, Laura A. Sanagorski; Lamm, Alexa J.; Rumble, Joy N. (EDIS, 2018)
Water quality and quantity are major issues in the state of Florida, and water resources can be affected by the way residents choose to fertilize and irrigate their lawns and landscapes. This 4-page document discusses the use of videos to promote good landscape management behaviors. Written by Laura A. Sanagorski Warner, Alexa J. Lamm, and Joy N. Rumble and published by the Department of Agricultural Education and Communication, May 2018. http://edis.ifas.ufl.edu/wc302